Poricoic acid A administered during DSS exposure attenuates acute colitis in mice and is accompanied by barrier-associated changes and endpoint fecal microbiota shifts - Mei Wang; Kunkun Zhang; Danli Wang; Mingtao Cao; Rong Yong; Xiangqian Li; Wenyi Chen; Chengcheng Peng; Jiale Chang; Lu Fang; Feiyang Zhou; Yuyue Wan; et al. (Journal of Natural Medicines, 2026)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Editorial Expression of Concern: Induction of Human Bone Marrow Mesenchymal Stem Cells Differentiation into Neural-Like Cells Using Cerebrospinal Fluid - Ying Ye; Yin-Ming Zeng; Mei-Rong Wan; Xian-Fu Lu (Cell Biochemistry and Biophysics, 2023)

Hsa_circ_0070194 targets the miR-384/HDAC2 axis to enhance proliferation, cell cycle, migration and invasion of trophoblast cells - Huan Chen; Cheng Gao; Wenhui Zhu; Rong Wan; Mei Xiong (Molecular & Cellular Toxicology, 2022)

Differential metabolism-associated gene expression of duck pancreatic cells in response to two strains of duck hepatitis A virus type 1 - Zhen Chen; Shao-hua Shi; Yu Huang; Cui-qin Huang; Rong-chang Liu; Long-fei Cheng; Guang-hua Fu; Hong-mei Chen; Chun-he Wan; Qiu-ling Fu (Archives of Virology, 2021)
Several outbreaks of duck hepatitis A virus type 1 (DHAV-1), which were characterized by yellow coloration and hemorrhage in pancreatic tissues, have occurred in China. The causative agent is called pancreatitis-associated DHAV-1. The mechanisms involved in pancreatitis-associated DHAV-1 infection are still unclear. Transcriptome analysis of duck pancreas infected with classical-type DHAV-1 and pancreatitis-associated DHAV-1 was carried out. Deep sequencing with Illumina-Solexa resulted in a total of 53.9 Gb of clean data from the cDNA library of the pancreas, and a total of 29,597 unigenes with an average length of 993.43 bp were generated by de novo sequence assembly. The expression levels of D-3-phosphoglycerate dehydrogenase, phosphoserine aminotransferase, and phosphoserine phosphatase, which are involved in glycine, serine, and threonine metabolism pathways, were significantly downregulated in ducks infected with pancreatitis-associated DHAV-1 compared with those infected with classical-type DHAV-1. These findings provide information regarding differences in expression levels of metabolism-associated genes between ducks infected with pancreatitis-associated DHAV-1 and those infected with classical-type DHAV-1, indicating that intensive metabolism disorders may contribute to the different phenotypes of DHAV-1-infection.

Correction to: Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Effect of fermentation bed on bacterial growth in the fermentation mattress material and cecum of ducks - Jian- mei Wang; Xin- meng Gan; Fa-jun Pu; Wan- xia Wang; Min Ma; Ling-li Sun; Ji-wei Hu; Bo Hu; Rong-ping Zhang; Li-li Bai; Liang Li; He-he Liu (Archives of Microbiology, 2021)

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

The accumulation and fractionation of Rare Earth Elements in hydroponically grown Phytolacca americana L. - Ming Yuan; Mei-Na Guo; Wen-Shen Liu; Chang Liu; Antony van der Ent; Jean Louis Morel; Hermine Huot; Wan-Ying Zhao; Xian-Ge Wei; Rong-Liang Qiu; Ye-Tao Tang (Plant and Soil, 2017)

Development of a Time-Resolved Fluorescence Immunoassay for the Diagnosis of Hepatocellular Carcinoma Based on the Detection of Glypican-3 - Juan-Juan Chen; Chun-Mei Xie; Cong-Rong Wang; Yong Wan; Zhi-Ning Dong; Ming Li; Wei-Wen Xu (Journal of Fluorescence, 2017)

Optimized culture medium for the production of flavonoids from Orostachys cartilaginea V.N. Boriss. callus cultures - Wan Bo Zhang; Xuan Chun Piao; Jin Rong Li; Ying Hua Jin; Mei Lan Lian (In Vitro Cellular & Developmental Biology - Plant, 2017)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

An Observational Study of Autologous Bone Marrow-Derived Stem Cells Transplantation in Seven Patients with Nervous System Diseases: A 2-Year Follow-Up - Chao Ren; Run-lu Geng; Wei Ge; Xiao-Yun Liu; Hao Chen; Mei-Rong Wan; De-Qin Geng (Cell Biochemistry and Biophysics, 2014)

Induction of Human Bone Marrow Mesenchymal Stem Cells Differentiation into Neural-Like Cells Using Cerebrospinal Fluid - Ying Ye; Yin-Ming Zeng; Mei-Rong Wan; Xian-Fu Lu (Cell Biochemistry and Biophysics, 2011)

Evaluation of the hepatoprotective and antioxidant activities of Rubus parvifolius L. - Jie Gao; Cui-rong Sun; Jie-hong Yang; Jian-mei Shi; Yue-guang Du; Yu-yan Zhang; Jin-hui Li; Hai-tong Wan (Journal of Zhejiang University-SCIENCE B, 2011)